STUDI BIOKULTUR KOMBUCHA UNTUK PENGEMBANGAN MATERIAL BANGUNAN LEMBARAN TERURAI HAYATI - Lianto, Fermanto; Trisno, Rudy; Husin, Denny (Universitas Tarumanagara, 2021)
Bioculture development in Indonesia is considered limited in comparison to its global phenomena. It is influenced by Western culture and mainly dictated by market demand. Indonesian advanced bio culture development is dominated by food technology. Few focus on the fashion industry, while the rest is categorized as a traditional home industry. Although Indonesia has many natural and cultural potencies, bio culture has not been developed progressively, especially building material. One of the most promising organic materials that are currently trending is kombucha. It is locally and globally popular in the current situation for herbal tea and cosmetic consumption. Although it is traditionally known for herbal tea production, kombucha SCOBY (Symbiosis Culture of Bacteria and Yeast) is also potentially developed as a synthetic material. It has great economic value, unique character and can be created at home. This paper investigates other benefits of kombucha beyond natural remedies. It is planned to be developed at home by anyone as an alternative building material. The research concentrates on developing kombucha SCOBY as a sheet for making a raw sample for building material and another product design. An experimental method is used by modifying conventional and traditional methods for kombucha brewing. This research emphasizes the variety of nutrients in the form of nutrient solutions and bio culture productivity. This research proves that to produce quality SCOBY. The determinants are a starter, medium (tea and sugar), and room quality, respectively. In the trial, only green tea and black tea that produced SCOBY met the sample criteria. In this trial, the results show that the sample quality is equivalent to paper or leather. It can be developed into wallpaper, space dividers, synthetic leather, and edible food packaging.Keywords: building; bio culture; biodegradable; kombucha; material.AbstrakPengembangan biokultur untuk material bangunan di Indonesia masih sangat terbatas dan digeneralisasi oleh tren mancanegara. Umumnya perkembangan biokultur terdikte oleh permintaan industri dan langka dikembangkan dalam skala rumah tangga. Industri rumahan saat ini lebih banyak didominasi pangan dan sandang daripada papan dan dikelola secara tradisional. Padahal Indonesia memiliki potensi kekayaan material alam dan budaya yang beragam, khususnya biokultur perlu mendapatkan kesempatan dalam pengembangan material bangunan baik untuk kebutuhan harian maupun potensi skala lebih besar. Jamur kombucha adalah salah satu material organik yang cepat berkembang dan tersedia di seluruh pelosok negri. Nilai ekonomis, karakter yang unik dan dapat dikembangkan di rumah merupakan salah satu potensinya, sementara masalahnya material ini sensitif, kurang menarik secara visual dan perlu pengelolaan khusus. Penelitian ini bermaksud mengekplorasi potensi lain biokultur kombucha sebagai bahan bangunan terurai hayati dari sekedar minuman tradisional. Metode percobaan eksperimental melalui pengembangan metode primordial yakni fermentasi berskala rumah tangga: mengeksplorasi pertumbuhan jamur dengan media bervariasi dan menghasilkan material bangunan berupa lembaran. Penelitian ini menekankan pada variasi nutrisi berupa larutan bernutrisi dan produktivitas biokultur. Penelitian ini membuktikan bahwa untuk menghasilkan SCOBY (Symbiosis Culture of Bacteria and Yeast) yang berkualitas, faktor penentu secara berurutan adalah: starter, media (teh dan gula) dan kualitas ruangan. Pada uji coba hanya teh hijau dan teh hitam yang menghasilkan SCOBY memenuhi kriteria sampel. Pada uji coba ini hasil menunjukkan kualitas sampel setara kertas atau kulit sehingga berpotensi dikembangkan menjadi wallpaper, pembatas ruang, kulit sintetis dan kemasan makanan yang bersifat edible.